2018
DOI: 10.18203/2394-6040.ijcmph20183575
|View full text |Cite
|
Sign up to set email alerts
|

The association between pulmonary function test and anthropometric measurements using bioelectric impidence analysis in adolescents

Abstract: Background: The development of pulmonary functions and growth of physical parameters i.e. height and weight are coexistent. These physical parameters are further affected by nutrition and physical activities of children. The aim of present study was to find correlation between pulmonary function test and anthropometric measurements using bioelectric impedance analysis in adolescence.Methods: A cross sectional observational study conducted at Sanskar Madhmik Vidhylay, Mayur Park, Aurangabad during July to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The positive correlation of height with PFT probably makes the height of asthmatic and allergic patients a good prognostic indicator for assessing compliance and disease control. The anthropometric measurements of weight, height, hip circumference and body surface area have been found to be positively correlated to the pulmonary function tests [16,17] . Nystad et al prepared a linear regression model which showed that standing height was a satisfactory predictor of lung function and the explained fraction of variance (R2) was 59% for FEV1 [18] .…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation of height with PFT probably makes the height of asthmatic and allergic patients a good prognostic indicator for assessing compliance and disease control. The anthropometric measurements of weight, height, hip circumference and body surface area have been found to be positively correlated to the pulmonary function tests [16,17] . Nystad et al prepared a linear regression model which showed that standing height was a satisfactory predictor of lung function and the explained fraction of variance (R2) was 59% for FEV1 [18] .…”
Section: Discussionmentioning
confidence: 99%